Palaeo-environmental archive of groundwater–surface water interaction zone, the Kebara wetlands, Carmel coast, Israel. (7th March 2016) - Sivan, Dorit; Greenbaum, Noam; Cohen-Seffer, Ronit; Sisma-Ventura, Guy; Almogi-Labin, Ahuva; Porat, Naomi; Melamed, Yoel; Boaretto, Elisabetta; Avnaim-Katav, Simona
Abstract: The Holocene sequence of the Kebara wetlands, a groundwater–surface water interaction zone ecosystem, was studied in a borehole (Core A), retrieved from the eastern trough of the Carmel coast of Israel. A multi-proxy approach was used for environmental reconstruction, and new ages were added for reassessment of the chronology. The fauna (mainly ostracods), flora, and palaeo-salinity estimates indicate marginal wetland that experienced shrinkage and enlargement, reflecting changing hydrological and climatic conditions. New luminescence ages of sediments and radiocarbon dating of terrestrial seeds in the upper part of the sequence provide a more reliable and accurate chronology. The lower part of the core, between about 14, 000 and about 7000 BP, indicates mainly wetter conditions, while the upper part, dated to the last 7000 BP, suggests drier conditions in general, with a few wetter episodes. The almost total disappearance of the fauna in the core after about 6000 BP is in agreement with regional climate records that document increasing aridity in the Levant. A comparison of modern δ 18 O and δ 13 C (water and ostracod) values from the Timsah ponds, the present remnants of the wetland, with the values derived from ostracods in the drilling indicates that, like today, the past wetlands were fed mainly by the karstic carbonate-rich Yarkon-Taninnim mountain aquifer. This paper emphasizes the importance of understanding the sources of the water feeding the wetlands for the re-assessment of previous chronology that was based on total organic carbon (TOC) 14 C dating.